The Impact of the Quality of Facilities and Infrastructure on Student Discipline in Islamic Boarding Schools - Anna Vanista (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to describe the quality of facilities and infrastructure, and analyze the level of discipline of students, as well as examine the effect of the quality of facilities and infrastructure on the discipline of students at Sabilil Muttaqien Islamic Boarding School and focused on the quality of infrastructure and discipline of students at Sabilil Muttaqin Islamic Boarding School. Then in this study using qualitative methods with research subjects to leaders and this research was conducted at the Sabilil Muttaqien Islamic Boarding School using data collection techniques through observation, interviews, and documentation methods. Therefore, the results of research at the Sabilil Muttaqien Islamic Boarding School found that the facilities and infrastructure at the Sabilil Muttaqien Islamic Boarding School are quite adequate and feasible in supporting the learning process, religious activities, and self-development of students. The level of discipline of santri is generally classified as good, indicated by compliance with rules, participation in routine activities, and behavior that reflects awareness and personal responsibility. However, there are still a small number of students who commit violations such as skipping class or leaving without permission, which are generally influenced by external factors such as the influence of social media and family parenting, therefore the discipline of students needs to be improved with an approach according to the times including in supervision related to the impact of using social media on student behavior and the Pondok continues to foster discipline through various religious programs and positive activities. Adequate facilities and infrastructure play an important role in creating an environment that supports character building and increasing student discipline.